From snorkelers to scuba divers in the elementary science classroom strategies and lessons that move students toward deeper learning - Almarode, John; Miller, Ann M. (Ann Marie) (Corwin, a SAGE Company, 2018)
"The contents of From Snorkelers to Scuba Divers teachers as they respond to the recent attention on American students' performance in science relative to the rest of the world, as well as the many initiatives to improve the performance of students in the learning of science, focusing specifically on the K-5 classroom. The strategies presented throughout the text target specific science skills and concepts presented in the Next Generation Science Standards (NGSS). Skills and concepts vary from chapter to chapter to ensure each grade level and area within science (i.e., Earth and Space, Life, Physical Sciences) are represented. Furthermore, connections are made between the NGSS and Common Core Standards in both mathematics and literacy"--